Effect of Banana Stem Liquid Organic Fertilizer On Shallot Growth And Production (Allium ascalonicum L.): Pengaruh POC Batang Pisang Terhadap Pertumbuhan Dan Produksi Bawang Merah (Allium ascalonicum L.) - Novianto, Wahyu; Prihatiningrum, Andriani Eko (Procedia of Engineering and Life Science, 2023)
The study-aims-to-determine-the-effect-of POC (liquid-organic-fertilizer) concentration of-banana-stems and-the interval of-application-of POC (liquid-organic-fertilizer) banana-stems on-the growth-and yield of onion plants. Conducted on private land, Tamanan Hamlet, Kepulungan Village, Gempol District, Pasuruan Regency from December 2022 to March 2023. Using factorial Group Randomized Design (RAK) and further tests using BNJ. The first-factor is-the concentration-of POC Banana Stems which-consists of-3 levels,-namely 100ml / L, 200ml / L, 300ml / L. while the-second-factor-is-the-interval-of-fertilizer-application-consisting of-3 levels,-namely-once-every-5-days,-once-every-10-days,-every-15-days, The-results-of variety analysis-show that-there is no-interaction between-the concentration of banana stem POC fertilizer and the time interval of POC fertilizer application. POC fertilizer concentration treatment has-a real-effect on observing plant-height, number-of bulbs and number-of POC fertilizer concentration treatment has-a real-effect on observing plant-height, number-of bulbs and number-of onion saplings, from banana stem POC fertilizer concentration treatment which can-produce-the-best wet weight-of shallots,-namely with a-concentration of 200ml/L.